Functionally suppressive CD8 T regulatory cells are increased in patients with multiple myeloma: a cause for immune impairment. - Karthick Raja Muthu Raja (PLoS ONE, 2012)
BACKGROUND: Multiple myeloma (MM) is a plasma cell malignancy frequently associated with impaired immune cell numbers and functions. In MM, several studies have previously shown that CD4 regulatory T (Treg) cells hamper effector T cell functions and enhance immune dysfunction. In this study, we aimed to prove the presence of functionally suppressive Treg cells expressing CD8 phenotype (CD8 Treg cells) in MM. To the best of our knowledge, this has not been reported previously in MM. METHODS: We analyzed CD8 Treg cells and their transcription factor FoxP3 from 64 newly diagnosed MM patients using flow cytometry and real time-polymerase chain reaction (RT-PCR). RNA profile of cytokines in CD8 Treg cells was also assessed using RT-PCR. CD8 Treg cells from 5 MM patients and 5 healthy donors were functionally evaluated using proliferation assays. RESULTS: CD8 Treg cells (CD8+CD25hi+) were significantly elevated in MM patients (P<0.0001), and their transcription factor FoxP3 expression was also higher in MM (P<0.0001) compared to healthy donors which was evidenced by flow cytometry and RT-PCR analyses. CD8 Treg cells negatively correlated with total lymphocyte count (P = 0.016). Functional studies revealed that CD8 Treg cells isolated from MM patients and healthy donors inhibited proliferation of CD4 T cells in a concentration dependent manner. In the presence of CD8 Treg cells in proliferation assays, level of IFN-γ was decreased but not IL-10. CD4 T cells from MM patients secreted abnormal level of IL-10 compared to healthy donors (P = 0.01) in proliferation assays without CD8 Treg cells. RNA profile of cytokines from CD8 Treg cells did not differ significantly between MM patients and healthy donors. CONCLUSIONS: These findings show the presence of increased number of functionally suppressive CD8 Treg cells in MM patients. We believe that these suppressive CD8 Treg cells might enhance immune impairment and disease progression in MM.